2016
DOI: 10.1159/000446921
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sirtuin 1 Gene rs10997870 Polymorphism and Suicide Behaviors in Bipolar Disorder

Abstract: Background/Aims: Suicidal behavior (SB) in bipolar disorder (BD) is a complex multifactorial event resulting from an interaction of genetic, neurobiological and psychosocial factors. Recent studies identified new possible mechanisms, suggesting a role for sirtuins (SIRTs 1-7), a family of nicotinamide adenine dinucleotide-dependent enzymes with a multifaceted role in the central nervous system. The aims of the present study were: (1) to investigate the effects of the rs10997870 SIRT1 gene variant on SB in BD; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…However, SIRT1 modulates several biological mechanisms, including oxidative stress regulation within the brain [45-47]. Therefore, all these processes may contribute to the observed association between SIRT1 and the depression-like phenotype [48, 49]. In the Italian subsample, COMT rs174696 was also associated with depression, partially supporting our hypothesis about oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…However, SIRT1 modulates several biological mechanisms, including oxidative stress regulation within the brain [45-47]. Therefore, all these processes may contribute to the observed association between SIRT1 and the depression-like phenotype [48, 49]. In the Italian subsample, COMT rs174696 was also associated with depression, partially supporting our hypothesis about oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…Other studies have shown that preventing SIRT1 in the NAc relieves stress-induced depressive-like behaviors 36 and attenuates drug self-administration 34 , 35 , 38 . Thus targeting of SIRT1 or NAD+ dependent pathways may have therapeutic implications for those with comorbid mood, substance use, and metabolic disorders 120 123 .…”
Section: Discussionmentioning
confidence: 99%
“…SIRTs have been shown to play important roles in cerebral ischemia (Zhang et al, 2011;Yang et al, 2013;Khoury et al, 2018), drug addiction (Renthal et al, 2009;Ferguson et al, 2015;Engel et al, 2016), synaptic plasticity (Herskovits and Guarente, 2014;Kim et al, 2019;Zhang et al, 2019), and cognition and aging (Kim et al, 2007;Gao et al, 2010;Zhang et al, 2011). Recent studies have suggested that SIRT1, SIRT2, and SIRT6 are associated with anxious and depressive disorders (Porcelli et al, 2013;Abe-Higuchi et al, 2016;Kim et al, 2016;Nivoli et al, 2016). CeA is known for its role in the regulation of emotional behaviors and modulation of pain (Veinante et al, 2013;Thompson and Neugebauer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT2 knockout blocks the development of social defeat stress-induced depression-like behavior (Zhang et al, 2018). Clinical studies also suggest that SIRT1 and SIRT2 gene polymorphisms are associated with depressive disorder (Porcelli et al, 2013;Nivoli et al, 2016), and decreased expression of SIRT1, SIRT2, and SIRT6 genes has been found in patients with a mood disorder (Abe et al, 2011;Luo and Zhang, 2016). These data suggest that SIRT1, SIRT2, and SIRT6 in different brain regions play important roles in the emotional disorders.…”
Section: Introductionmentioning
confidence: 92%